2021
DOI: 10.5858/arpa.2020-0830-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics and Outcome Descriptors of Metaplastic Breast Carcinoma

Abstract: Context.— Metaplastic breast carcinoma is an aggressive form of breast cancer that accounts for 0.5% to 3% of all breast cancers. Objective.— To study the clinicopathologic characteristics and outcomes of this rare disease. Design.— Retrospective study of patients with a diagnosis of metaplastic breast carcinoma between 2000 and 2019. Hematoxylin-eosin–staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These emphasizes that we might need to consider to the effect of non-biologic stressors on the disease in the future. However, additional multicenter studies are needed to further characterize these findings ( Abada et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These emphasizes that we might need to consider to the effect of non-biologic stressors on the disease in the future. However, additional multicenter studies are needed to further characterize these findings ( Abada et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports, including our study, have found the mixed subtype to be an unfavorable factor [ 12 , 13 , 15 , 16 ]. Many authors regarded tumor size was correlated with survival [ 12 , 13 , 15 , 23 , 24 ]. However, one multi-center research indicated that only lymph node status and lymphovascular invasion influenced prognosis, not tumor size and histological grade [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…MpBC has little response to NAC, with previous studies showing the pCR rate in the range of 0–17% [ 7 , 15 , 16 , 23 , 24 , 39 ]. A recent prospective trial (NCT02276443) showed the pCR rate reaching 23% [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described our experience with MBC as a rare subtype of breast cancer. [ 10 ] However, in the current study, we have provided additional clinical information on the relevance of ER status in MBC, given that most cases are triple-negative. Following our review, the median age at diagnosis for all MBC patients was 57 years and this finding is similar to what has been previously reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…We searched our institution’s database between January 2000 and April 2019 to identify patients diagnosed with MBC during this time. As previously reported, search terms used included “metaplastic breast carcinoma”, “carcinosarcoma”, “breast carcinoma with metaplasia”, “squamous cell carcinoma”, “spindle cell carcinoma”, “carcinoma with sarcomatoid metaplasia”, “carcinoma with osseous or bony metaplasia”, “carcinoma with chondroid metaplasia”, and “breast carcinoma with osteoclastic giant cells.” [ 10 ] We reviewed patient’s demographic information, tumor characteristics (tumor size, histologic differentiation, tumor focality, histologic grade, lymphovascular invasion, lymph node metastasis, distant metastasis, estrogen receptor [ER], progesterone receptor [PR], human epidermal receptor-2[(HER-2], Ductal Carcinoma in situ [DCIS], and fibrocystic breast disease), comorbidity (obesity, smoking, history of prior cancers), treatment received, and OS. [ 10 ] Clinical tumor size was based on the largest size recorded by gross pathologic examination.…”
Section: Methodsmentioning
confidence: 99%